Identifying corn leaves diseases by extensive use of transfer learning: a comparative study - Ahmed Samit Hatem; Maha Sabri Altememe; Mohammed Abdulraheem Fadhel (Institute of Advanced Engineering and Science, 2023)
Deep learning is currently playing an important role in image analysis and classification. Diseases in maize diminish productivity, which is a major cause of economic damages in the agricultural business throughout the world. Researchers have previously utilized hand-crafted characteristics to classify images and identify leaf illnesses in Maize plants. With the advancement of deep learning, researchers can now significantly enhance the accuracy of object classification and identification. Using the